Research on the Programmes Reformation of Bachelor Degree in Investment in Applied Universities: Based on the ‘Double Carbon’ Goal - Wang, Wenxue; Pang, Huiyi; Zhang, Zheng (Transactions on Social Science, Education and Humanities Research, 2023)
With the goals of ‘carbon peaking’ and ‘carbon neutrality’ proposed, society’s requirements for the educational achievements of applied universities have also changed. In the context of frequent extreme weather, the impact of climate change, and the development of big data technology, students in the contemporary higher education system should improve their all-round abilities to boost their Curriculum Vitae (CV) for job hunting and even for further study in postgraduate. Especially for undergraduates majoring in investment, it is both an opportunity and a challenge. The development directions of investment products, such as diversification, greenness, and technological intelligence are all self-development directions as well as career planning paths that students majoring in investment grasp. In the process, applied undergraduate universities should help students become new-era talents that meet the requirements of the ‘dual carbon’ goal from the following aspects: i) Establish a teaching system with green finance as the core module ii) Strengthen school-enterprise cooperation to promote investment to improve the practical ability of students majoring in investment and set career planning goals iii) Pay attention to the cultivation of comprehensive abilities of students majoring in investment to adapt to the rapidly developing international financial market and complex financial environment as soon as possible in their careers.